2015
DOI: 10.1007/978-3-319-15368-1_21
|View full text |Cite
|
Sign up to set email alerts
|

The Distributed Ontology, Modeling and Specification Language – DOL

Abstract: Abstract. There is a diversity of ontology languages in use, among them OWL, RDF, OBO, Common Logic, and F-logic. Related languages such as UML class diagrams, entity-relationship diagrams and object role modelling provide bridges from ontology modelling to applications, e.g. in software engineering and databases. Another diversity appears at the level of ontology modularity and relations among ontologies. There is ontology matching and alignment, module extraction, interpolation, ontologies linked by bridges,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 14 publications
(20 reference statements)
0
39
0
Order By: Relevance
“…Also, higher initial levels of depression were recorded among girls, and were associated with a slower decrease in depressive symptoms in early adulthood. Similarly, Mossakowski et al (2013) examined the effect of poverty on depression in early adulthood using data from the National Longitudinal Survey of Youth (NLSY). The results suggested that chronic exposure to poverty as well as female gender and prior mental health issues were predictive of depressive symptoms in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Also, higher initial levels of depression were recorded among girls, and were associated with a slower decrease in depressive symptoms in early adulthood. Similarly, Mossakowski et al (2013) examined the effect of poverty on depression in early adulthood using data from the National Longitudinal Survey of Youth (NLSY). The results suggested that chronic exposure to poverty as well as female gender and prior mental health issues were predictive of depressive symptoms in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the alignment between the process-related ontology modules in VFDM and the PSL ontology will be addressed. Ontohub ontology repository is a platform that can support such alignment and consistency checking of linked ontologies, by exploiting the parsing and inference back end of the Heterogeneous Tool Set [26]. Finally, the potentiality of reasoning will be investigated to assess the integrity and consistence of a production system model, as for example addressed by Abele et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…11 The theoretical underpinnings of the DOL language have been described in detail in (Kutz, Mossakowski, and Lücke, 2010) and (Mossakowski, Lange, and Kutz, 2012), whilst a full description of the language can be found in (Mossakowski et al, 2015) or (in a more condensed form) in (Mossakowski et al, 2013). Building on similar ideas to those underlying the first-order ontology repository COLORE 12 (Grüninger et al, 2012), we propose to capture image schemas as interrelated families of (heterogeneous) theories.…”
Section: Image Schema Families As Graphs Of Theoriesmentioning
confidence: 99%